New Exercise-Dipyridamole Combined Test for Nuclear Cardiology in Insufficient Effort: Appropriate Diagnostic Sensitivity Keeping Exercise Prognosis - Vidal,Inés (2015)
Abstract Background: Myocardial perfusion scintigraphy (MPS) in patients not reaching 85% of the maximum predicted heart rate (MPHR) has reduced sensitivity. Objectives: In an attempt to maintain diagnostic sensitivity without losing functional exercise data, a new exercise and dipyridamole combined protocol (EDCP) was developed. Our aim was to evaluate the feasibility and safety of this protocol and to compare its diagnostic sensitivity against standard exercise and dipyridamole protocols. Methods: In patients not reaching a sufficient exercise (SE) test and with no contraindications, 0.56 mg/kg of dipyridamole were IV administered over 1 minute simultaneously with exercise, followed by 99mTc-MIBI injection. Results: Of 155 patients, 41 had MPS with EDCP, 47 had a SE test (≥ 85% MPHR) and 67 underwent the dipyridamole alone test (DIP). They all underwent coronary angiography within 3 months. The three stress methods for diagnosis of coronary lesions had their sensitivity compared. For stenosis ≥ 70%, EDCP yielded 97% sensitivity, SE 90% and DIP 95% (p = 0.43). For lesions ≥ 50%, the sensitivities were 94%, 88% and 95%, respectively (p = 0.35). Side effects of EDCP were present in only 12% of the patients, significantly less than with DIP (p < 0.001). Conclusions: The proposed combined protocol is a valid and safe method that yields adequate diagnostic sensitivity, keeping exercise prognostic information in patients unable to reach target heart rate, with fewer side effects than the DIP.